USING INFORMATION AND COMMUNICATION TECHNOLOGIES BY TEACHING MATHEMATICAL SCIENCES IN PEDAGOGICAL UNIVERSITIES - Bekzod Alimov (Web of Journals Publishing, 2024)
The article examines the influence of information and communication technologies on the educational process of higher education. Based on the strategic tasks of the Higher Education Development Concept until 2030, the possibilities of modern forms of educational process organization and digital technologies were analyzed. The purpose of the ideas put forward in the article is to effectively use ICT opportunities and increase the quality of education.
Keywords: Higher education, information and communication technologies, digital technologies, quality and efficiency of education, Internet.